ALVO: a collective platform for volcanic risk reduction in Latin America - Pablo Forte; Daniel Bertin; Lizzette Rodriguez; Mariana Patricia Jácome Paz; Silvana Hidalgo; Yemerith Alpizar-Segura; Guillermo E. Alvarado; Constanza Perales Moya; José Luis Palma; José G. Viramonte; Hugo Delgado-Granados (Journal of South American Earth Sciences, 2026)

Living on top of a volcanic-hydrothermal system: the case of Copahue village, Argentina - María Clara Lamberti; Pablo Forte; Joaquín Llano; Nicolás Nuñez; Daniel Sierra; Fabricio Carbajal; Lucas Guerriero; Nicolás Alarcón; Martín Gómez; Sebastián García; Mariano Agusto (Natural Hazards, 2026)

Seed banking of mediterranean coastal plants: an analysis to identify current seed availability and gaps to guide future seed collection and habitat restoration activities - Marcello De Vitis; Valter Di Cecco; Mohamed Abdelaal; Gianluigi Bacchetta; Jože Bavcon; Kenza Saadiya Benmenni; Maurizio Bianchelli; Magda Bou Dagher Kharrat; Joseph A. Buhagiar; Francesca Carruggio; Angelino Carta; Simona Casavecchia; et al. (Journal of Coastal Conservation, 2025)

Daylight photodynamic inactivation of cattle tick Rhipicephalus microplus by porphyrins: An alternative for the ectoparasite control - Isabela Castro Pereira Gomes; Lorena Dias Amor Divino; Fernanda Meneses Rodrigues; Cinthya Marques Fortes Fleury; Eli Silveira Alves Ducas; Jaqueline Cristine Desordi; Bernardo Almeida Iglesias; Ricardo Costa Santana; Caio Márcio Oliveira Monteiro; Welber Daniel Zanetti Lopes; Pablo José Gonçalves; Guilherme Rocha Lino Souza (Journal of Photochemistry and Photobiology B: Biology, 2024)

The lifecycle of volcanic ash: advances and ongoing challenges - Joali Paredes-Mariño; Pablo Forte; Stefano Alois; Ka Lok Chan; Valeria Cigala; Sebastian B. Mueller; Matthieu Poret; Antonio Spanu; Ines Tomašek; Pierre-Yves Tournigand; Diego Perugini; Ulrich Kueppers (Bulletin of Volcanology, 2022)
Explosive volcanic eruptions can produce vast amounts of volcanic ash made up mainly of fragments of magmatic glass, country rock and minerals < 2 mm in size. Ash particles forming from magma fragmentation are generated by several processes when brittle response accommodates (local) deformation stress that exceeds the capability of the bulk material to respond by viscous flow. These processes span a wide range of temperatures, can occur inside or outside the volcanic edifice and can involve all melt compositions. Ash is then dispersed by volcanic and atmospheric processes over large distances and can have global distributions. Explosive eruptions have repeatedly drawn focus to studying volcanic ash. The continued occurrence of such eruptions worldwide and their widespread impacts motivates the study of the chemical and physical processes involved in the lifecycle of volcanic ash (e.g. magma fragmentation, particle aggregation), as well as the immediate to long-term effects (e.g. water and air pollution, soil fertilization) and consequences (e.g. environmental, economic, social) associated with ashfall. In this perspectives article, we reflect on the progress made over the last two decades in understanding (1) volcanic ash generation; (2) dispersion, sedimentation and erosion; and (3) impacts on the atmosphere, hydrosphere, biosphere and modern infrastructure. Finally, we discuss open questions and future challenges.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Correction to: Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.